Effect of Low-Stress Fatigue on the Off-Crack-Plane Fracture Energy in Engineered Cementitious Composites - Longlong Liu; Shuling Gao; Jianda Xin; Dahai Huang (Advances in Civil Engineering)
This paper presented an experimental study on the flexural properties of engineered cementitious composites (ECCs). The bending fatigue damage, residual deformation, and damage characteristics were investigated after a certain number of low stress levels in fatigue load. The composite fracture energy and fiber-bridging fracture energy were calculated by the J integral. It is observed that the number of cracks increased with the increment of stress levels, and most of the cracks were formed during the earlier stage of the dynamic test. The deformation capability decreased with the increment of stress levels while the reduction of the ultimate load was minor after the dynamic load. Furthermore, the strain-hardening phenomenon of the specimen enhanced initially and then weakened with the increment of stress levels. The residual equivalent yield strength became smaller with the increase of stress levels. Meanwhile, the trend was mild at low stress levels and then became steep at high stress levels.